Monitoring Effectiveness of an Operational Project on Two Threatened Landbirds: Applying a Before–After Threat Analysis and Threat Reduction Assessment - Corrado Battisti; Marisa Perchinelli; Sharon Vanadia; Pietro Giovacchini; Letizia Marsili (Land, 2023)
Human activities are at the origin of anthropogenic threats altering ecosystems at any hierarchical level. To mitigate them, environmental managers develop projects to obtain effective outcomes on biological targets of conservation concern. Here, we carried out two new approaches (TAN = Threat Analysis and TRA = Threat Reduction Assessment) aimed at assessing the effectiveness of conservation actions on two threatened beach-nesting landbird species, the Kentish Plover (Charadrius alexandrinus) and the Little Ringed Plover (C. dubius), breeding along a coastal beach of central Italy. Using a score-based evaluation (TAN approach), a panel of experts assessed the extent, intensity, and magnitude of a set of species-specific threats, ranking them from more to less impacting. Domestic dogs, dune trampling, and synanthropic predators appeared as the threats with the most significant magnitudes. Using the TRA approach, experts obtained a rank of threats that were more urgent to solve: i.e., domestic dogs and dune trampling. To contrast with these threats, in 2021, we carried out a conservation project with specific measures that were aimed at reducing the threat magnitude on birds. They included: dune borders demarcation, anti-predatory cages on plover nests, the removal of beach-stranded fishing lines and hooks, field surveillance by volunteers, dog control, social- and mass-media communication, and alliances with stakeholders and institutions. After the project, mechanical beach grooming (>80%), dune trampling, and synanthropic predators (both >60%) showed the highest percentage of impact reduction. The project showed a medium–high level of effectiveness in reducing the total threat magnitude (TRA-I index = 63.08%). The Threat Analysis should be routinely used to arrange a causal chain that is useful for defining the relationships among human-induced threats and ecological targets, selecting the threats with the highest magnitudes. After the projects, the Threat Reduction Assessment may assess the level of threat reduction, suggesting measures for adaptive management.